Investigation of the p-GaN layer thickness of InGaN-based photoelectrodes for photoelectrochemical hydrogen generation. (23rd May 2019) - Iida, Daisuke; Shimizu, Takamitsu; Ohkawa, Kazuhiro
Abstract: We investigated photoelectrochemical hydrogen generation using InGaN-based photoelectrodes with different p-GaN layer thicknesses. It was confirmed that the photocurrent density and hydrogen generation can be enhanced at zero bias between the photoelectrode and counterelectrode. We found that the maximum energy conversion efficiency was 2.0% when using an InGaN-based photoelectrode with a 20-nm-thick p-GaN layer; this was one order larger than for a photoelectrode without a p-GaN layer. The p-GaN layer can pull the potential of the InGaN layer upward, leading to efficient electron–hole separation in the photoabsorption layer and improving carrier transfer from the InGaN layer. By measuring incident photon to current efficiency, it was confirmed that the InGaN layer worked as a photoelectrode since the absorption edge wavelength was around 400 nm.